Hedonic or utilitarian buying behaviours - what values do young adult customers seek in online group buying?. (13th April 2015) - Rudawska, Edyta; Petljak, Kristina; Stulec, Ivana
Nowadays, the value acquired by customers during shopping can be perceived in two dimensions: utilitarian and hedonic. In order to identify online group buying behaviour of young adult consumers, research was conducted among university students in Poland. The purpose of the research was to profile group buyers in Poland regarding their demographic and behavioural (hedonic or utilitarian) characteristics. Results of the performed statistical data analysis show some significant associations in group buying behaviour, while it is not possible to hypothesise regarding demographic characteristics of the respondents and their motivation for group buying. Further on, one of the contribution of this research lies in performed factor analysis by which it is possible to give more precise insights in online group buying behaviour according to hedonic or utilitarian buying behaviours.